Telephone delivery of psychological interventions: Balancing protocol with patient-centred care. (May 2021) - Drew, P.; Irvine, A.; Barkham, M.; Faija, C.; Gellatly, J.; Ardern, K.; Armitage, J.C.; Brooks, H.; Rushton, K.; Welsh, C.; Bower, P.; Bee, P.
Abstract: Common mental health problems of anxiety and depression affect significant proportions of the global population. Within the UK, and increasingly across western countries, a key policy response has been the introduction of high volume, low intensity psychological assessment and treatment services, such as the NHS's Improving Access to Psychological Therapies (IAPT) service, the largest service delivery model yet to be implemented at a national level (England). IAPT may be delivered in face-to-face meetings or over the telephone, as well as through other media. In order to increase access and achieve wide reach with efficient use of resources, IAPT's service models utilise relatively structured and standardised protocols, whilst aiming simultaneously to deliver a tailored and personalised experience for patients. Previous research has revealed that this can be a challenging balance for front-line practitioners to strike. Here we report research into the telephone delivery of guided self-help, low intensity interventions within IAPT, examining the challenges faced in remote delivery when combining structure with personalisation during assessment and treatment sessions. We show the ways in which the lack of flexibility in adhering to a system-driven structure can displace, defer or disrupt the emergence of the patient's story, thereby compromising the personalisation and responsiveness of the service. Our study contributes new insights to our understanding of the association between personalisation, engagement and patient experience within high volume, low-intensity psychological treatment services. Our research on the telephone delivery of IAPT is particularly timely in view of the current global Covid-19 health crisis, as a result of which face-to-face delivery of IAPT has had to be (temporarily) suspended. Highlights: Study of interaction in telephone delivery of NHS psychological therapy programme. Identifies challenges delivering patient-centred treatment in high volume service. Inflexibility administering protocols compromises personalised patient experience. Importance of eliciting patients' accounts of problems at earliest opportunity.